OC-063 Gut microbiota-host bile acid metabolism interactions in clostridium difficile infection: the explanation for the efficacy of faecal microbiota transplantation?. (17th June 2017) - Mullish, BH; McDonald, JAK; Kao, DH; Allegretti, JR; Petrof, EO; Pechlivanis, A; Barker, GF; Atkinson, SR; Williams, HRT; Thursz, MR; Marchesi, JR
Abstract : Introduction: Faecal microbiota transplantation (FMT) effectively treats recurrent Clostridium difficile infection (CDI), yet the mechanisms underlying its efficacy are poorly-defined. In vitro, conjugated primary bile salts (i.e. taurocholic acid) promote the germination of C. difficile, whilst secondary bile salts (i.e. deoxycholic acid) inhibit vegetative growth of the organism. As gut microbiota-derived enzymes (i.e. bile salt hydrolases (BSH)) are responsible for bile acid metabolism in vivo, we hypothesised that the efficacy of FMT may reflect transfer of BSH-producing bacteria, with restoration of a gut bile acid profile that inhibit germination/vegetative growth of C. difficile . Method: Faecal samples were collected from patients with recurrent CDI pre-FMT (n = 26), at 8–12 weeks after successful FMT, and also from stool donors (n = 17). Bacterial DNA was used for microbial profiling (via 16S rRNA gene sequencing) and for qPCR of BSH genes. Liquid chromatography-mass spectrometry was used for bile acid profiling. BSH enzyme activity was established using a plate-based precipitation assay. Results: Microbial and bile acid profiles from pre-FMT patients were markedly different to those found in the post-FMT and donor groups (p < 0.001, PERMANOVA); qPCR confirmed enrichment of BSH-producing organisms post-FMT. Taurocholic acid levels were elevated (and deoxycholic acid levels reduced) pre-FMT compared to donors and post-FMT (p < 0.001, Wilcoxon-Mann-Whitney test). By Spearman's rank, abundance of BSH-producing bacteria negatively correlated with taurocholic acid and positively correlated with deoxycholic acid levels (Figure 1), with p < 0.05 for this correlation for levels of both bile acids with Bacteroides vulgatus, Blautia obeum, Dorea longicatena, and Eubacterium rectale . Stool BSH activity was negligible pre-FMT, but was significantly increased post-FMT (p < 0.002, Wilcoxon-Mann-Whitney). Conclusion: The gut microbiota is enriched with BSH-producing bacterial species post-FMT for CDI, and these organisms are present within the gut microbiota of donors. The increased relative abundance of BSH-producing organisms post-FMT was negatively correlated with gut taurocholic acid levels, positively correlated with deoxycholic acid levels, and associated with increased BSH activity. These data collectively support a hypothesis of transfer of BSH-producing organisms during FMT linked to reconstitution of a gut bile acid profile unfavourable to the germination and growth of C. difficile . Disclosure of Interest: None Declared